2005
DOI: 10.1366/000370205775142656
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Laser Ablation of Metals Detected by Atomic Emission in a Microwave Plasma and by Inductively Coupled Plasma Mass Spectrometry

Abstract: It has been shown that an increase in sensitivity and selectivity of detection of an analyte can be achieved by tuning the ablation laser wavelength to match that of a resonant gas-phase transition of that analyte. This has been termed resonant laser ablation (RLA). For a pulsed tunable nanosecond laser, the data presented here illustrate the resonant enhancement effect in pure copper and aluminum samples, chromium oxide thin films, and for trace molybdenum in stainless steel samples, and indicate two main cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 77 publications
1
40
0
Order By: Relevance
“…Laser ablation is a well-known sample introduction technique for surface microanalysis (23), but the resolution of LA has traditionally been limited by the diameter of the incident laser beam. For example, in recent work performed by us (24)(25)(26), the ablation laser spot size was on the order of 100-200 mm. Significantly smaller sample volumes can be liberated from the surface of interest by use of an apertured or apertureless probe with nanoscale dimensions.…”
Section: Application Of the Near-field Effect To Nanoscale Laser Ablamentioning
confidence: 99%
“…Laser ablation is a well-known sample introduction technique for surface microanalysis (23), but the resolution of LA has traditionally been limited by the diameter of the incident laser beam. For example, in recent work performed by us (24)(25)(26), the ablation laser spot size was on the order of 100-200 mm. Significantly smaller sample volumes can be liberated from the surface of interest by use of an apertured or apertureless probe with nanoscale dimensions.…”
Section: Application Of the Near-field Effect To Nanoscale Laser Ablamentioning
confidence: 99%
“…Previous estimates for Saha ionization, carried out by Niu & Houk on a commercial plasma at atmospheric pressure, 31 assumes a plasma at LTE where T ÂŒ T i ÂŒ T e ÂŒ T gas ÂŒ 7500 K. However, Chen & Han assessed the Saha equation for a non-LTE plasma, 37 and found that T e is the appropriate temperature to use as an input for the non-LTE Saha equation, as electron collisions are the dominant mechanism of ionization. Therefore, we use the framework of the Saha equation established by Niu & Houk, 31 (eqn (8) and (9)) with values of T e converted to K (1 eV ÂŒ 11 600 K) input as the plasma temperature.…”
Section: Estimates For Analyte Ionizationmentioning
confidence: 99%
“…In the commercial realm, plasmas are routinely applied as robust and reproducible sources for optical emission spectra, 5,6 as well as ionized organic compounds and monoatomic ions for mass spectrometry. [7][8][9][10][11][12][13][14] Commercial inductively coupled plasmas (ICPs) operate at high power output (>1 kW) and ionize desolvated solutions or ablated geologic material. Recent advances in plasma technology demonstrate that low power plasma sources, operating at ambient or reduced pressure, perform direct desorption and ionization of molecular compounds or geologic materials in their native state, although the potential to atomize large particles remains poorly constrained.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of Cr(VI) in environmental samples is routinely carried out using analytical techniques, such as spectrophotometry [5], inductively coupled plasmaatomic emission spectrometry [6], atomic absorption spectrometry [7], high pressure liquid chromatography [8], X-ray fluorescence [9], and mass spectrometry [10]. However, these techniques always need extensive labor and analytical resources, which prohibit their use for rapid detection and field deployment [11].…”
Section: Introductionmentioning
confidence: 99%